Evaluasi Kurikulum Pembelajaran Bahasa Arab di SMA Islam Al Azhar 24 Boarding School - Ii Rahmanudin; M. Syahrul Anwar; Bakri Mohammad Bkhet Ahmad; Nur Qomari (Taqdir, 2022)
Abstract Over time, the curriculum in Indonesia continues to change, especially the curriculum at the Ministry of Education and Culture. This affects school policies in the application of the learning process. As is the case with the Arabic learning curriculum applied at Al Azhar 24 Baording School Islamic High School which is still applying the 2019 curriculum as a reference, especially in Arabic lessons. However, it is in contrast to its implementation in the field. Each school certainly has a different evaluation and is interesting to discuss. Therefore, the researchers tried to discuss how to implement the 2019 curriculum in Arabic language learning at Al Azhar 24 Baording Islamic High School, and to find out the evaluation of the implementation. This research uses descriptive qualitative method with a case study approach. The results of this study state that the evaluation of teacher understanding of the implementation of the 2019 curriculum is still very lacking, so that the effect on the learning process and assessment results is in gaps. Therefore, with boarding or boarding-based schools, it is necessary to develop an Arabic language learning curriculum at Al Azhar Islamic High School so that the four competencies of languages can be achieved. Keywords: Curriculum Evaluation, Arabic Learning